Political Role of Social Media as a Field of Research and as a Field of University Level Study - Dmitry Baluev (Journal of Social and Development Sciences, 2013)
This article is drawing out major approaches to the study of political role of social media. On the one hand, in a nearest future such researches could be one of the main hot topics of political analysis. On the other hand, this field of study is starting to be reflected in leading universities’ curriculum. However, common theoretical base for this field of study is still absent. An attempt to clarify terminology, picture out major approaches to the role of social media in politics, formulate major trends in this sphere of public life is made in this paper. It touches upon also consequences of rising political role of social media for foreign and security policy formulation. Possible applied use of this concept is a special interest for the author.